Association between age and malnutrition in oldest-old and centenarian populations - Qiao Zhu; Shasha Guan; Qun Li; Yangrui Zheng; Xiaobing Wang; Yali Zhao; Bing Zhu; Ping Ping; Youchen Zhang; Shihui Fu (BMC Geriatrics)
Abstract Background As the pace of social aging accelerates, mitigating malnutrition has emerged as a pressing public health imperative. This study aimed to assess the association between age and malnutrition in Chinese oldest-old and centenarian populations. Methods This population-based survey investigated 1768 adults in 18 cities and counties using a standardized protocol. Face-to-face interview was conducted by a well-trained team using home-visiting method. Results Logistic regression analyses demonstrated a significantly inverse association between age and malnutrition. Each one-year increase in age was associated with a significantly reduced likelihood without malnutrition [model 1: odds ratio (OR) 0.91, 95%confidence interval (CI) 0.90–0.92, p < 0.001; model 2: OR 0.94, 95%CI 0.92–0.96, p < 0.001). Restricted Cubic Spline revealed a linear correlation between age and malnutrition (model 1: p-overall ≤ 0.001, p-nonlinear = 0.011; model 2: p-overall ≤ 0.001, p-nonlinear = 0.079). Subgroup analyses indicated interaction effects of cigarette smoking (p = 0.002), red meat consumption (p = 0.028), and vegetable consumption (p = 0.009) on malnutrition. Conclusions This study demonstrated a linear association between age and malnutrition in Chinese oldest-old populations and indicated interaction effects of cigarette smoking, red meat consumption, and vegetable consumption on malnutrition. Food consumption is related to nutritional status as a key element in age-malnutrition association. An in-depth understanding of food and nutrition in older adults could help establish evidence-based recommendations to increase survival rate.